1985
DOI: 10.1128/iai.50.1.175-182.1985
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression associated with the development of chronic infections with Rickettsia tsutsugamushi: adherent suppressor cell activity and macrophage activation

Abstract: Measures of general immunocompetency such as lymphocyte responses to mitogens and alloantigens and the ability to produce antibody to T-dependent and T-independent antigens were evaluated during the development of chronic infections with Rickettsia tsutsugamushi resulting from subcutaneous infection of BALB/c mice. It was found that a transient immunosuppression was demonstrable regardless of the infecting strain of rickettsiae; however, the immunosuppression produced by the Karp and Kato strains was more pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
4
12
0
Order By: Relevance
“…It was found that a transient immunosuppression in mice was demonstrable in O. tsutsugamushi infection (20). Silvered leaf monkeys inoculated with O. tsutsugamushi produced early leukocytosis followed by leukopenia and significant decrease in packed-cell volume (37).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that a transient immunosuppression in mice was demonstrable in O. tsutsugamushi infection (20). Silvered leaf monkeys inoculated with O. tsutsugamushi produced early leukocytosis followed by leukopenia and significant decrease in packed-cell volume (37).…”
Section: Discussionmentioning
confidence: 99%
“…In chronic infections, organisms have evolved mechanisms to partially evade immune defenses. There are interesting parallels for chronic diseases caused by leishmaniae (10,14,32,42), trypanosomes (22,37,38,47), schistosomes (45,48,49,53), filariae (35), Mycobactenum leprae (46), Mycobactenum tuberculosis (40), Mycobactenum intracellulare (13), rickettsiae (21), and brucellae (12). An early acute stage of localized infection is typical.…”
Section: Chronic Infectionsmentioning
confidence: 99%
“…PGE2 plays an important role in normal down-regulation of different immune responses. In certain infections, such as those caused by M. leprae (46), M. intracellulare (13), and Rickettsia tsutsugamushi (21), macrophages oversecrete PGE2. This accelerates the process of normal down-regulation.…”
Section: Chronic Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing that prostaglandin production by monocytes is a component of immune dysfunction in CMC would have tremendous significance. This mechanism would (i) give the patient monocyte the role of suppressor cell (4), (ii) provide for the possibility that a suppressor T lymphocyte might also be involved (192), and (iii) allow classification of CMC with other chronic infections in which macrophages and T lymphocytes have a significant immunoregulatory role (19,24,41,70,71,87,103,113,126,130,177,181).…”
Section: Mechanisms Of Mannan-mediated Immunosuppressionmentioning
confidence: 99%